The added value of the ISO 9001:2015 international standard from an auditors’ perspective: a cb-sem based evaluation - Domingues, José Pedro (2020)
This research evaluates IRCA registered auditors’ perspectives of the added value of ISO 9001:2015 to the organizations that adopt it and are certified accordingly, bringing a more independent perspective than previous studies based on quality managers or consultants' views. Supported by a worldwide survey among IRCA registered auditors and the adoption of a Covariance based- Structural Equation Modelling (CB-SEM) approach the results point out that the auditors’ judgment regarding the ISO 9001:2015 value is influenced by their perceptions (regarding the document) and experience (auditing). The research results highlight the importance of selecting auditors with the appropriate ISO 9001:2015 knowledge and experience to assess ISO 9001:2015 Quality Management Systems (QMSs) within the certification process, therefore, contributing to the business and processes performance improvement and sustainable outcomes.